DEVELOPING STUDENT WORKSHEET USING STEM APPROACH IN THE TOPIC OF MATERIAL PRESSURE AND ITS APPLICATION - DIAN SRIANI DASOPANG; Arief Muttaqiin (Pendidikan IPA, FMIPA, UNP, 2023)
Based on preliminary studies, the interview that has been done to teachers and students, it was found that the learning process still needs to be optimized because the learning was still centered on the teacher and students were not actively involved in the learning process. From the initial studies through interviews and questionnaires to science teachers and students at SMP 2 Portibi, it was found that science teachers had not used the STEM approach worksheet teaching materials and some students still having difficulty understanding the matter of substance pressure and its application. This type of research is Research and Development (R&D) using the 4D model which consists of four stages: define, design, develop, and disseminate. Based on data analysis, it was found that the validity and practicality values ​​of the product with an average validity of 0,52 were in the medium category and the average practicality according to the teacher and students respectively was 0,97 and students 0,93 were in the very high category.